2020
DOI: 10.3390/w12113223
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning to Estimate Surface Soil Moisture from Remote Sensing Data

Abstract: Soil moisture is an integral quantity parameter in hydrology and agriculture practices. Satellite remote sensing has been widely applied to estimate surface soil moisture. However, it is still a challenge to retrieve surface soil moisture content (SMC) data in the heterogeneous catchment at high spatial resolution. Therefore, it is necessary to improve the retrieval of SMC from remote sensing data, which is important in the planning and efficient use of land resources. Many methods based on satellite-derived v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 114 publications
3
48
0
Order By: Relevance
“…A support vector machine (SVM) or its regression version, support vector regression (SVR), is a supervised machine learning algorithm, which is powerful and flexible for classification and regression [35]. Using an optimal kernel, SVM maps the input data into different classes in a hyperplane in multidimensional space in an iterative manner until it finds a maximum marginal hyperplane, in which the differences among classes are maximized so as to minimize the error of classification [34].…”
Section: Support Vector Regression (Svr)mentioning
confidence: 99%
“…A support vector machine (SVM) or its regression version, support vector regression (SVR), is a supervised machine learning algorithm, which is powerful and flexible for classification and regression [35]. Using an optimal kernel, SVM maps the input data into different classes in a hyperplane in multidimensional space in an iterative manner until it finds a maximum marginal hyperplane, in which the differences among classes are maximized so as to minimize the error of classification [34].…”
Section: Support Vector Regression (Svr)mentioning
confidence: 99%
“…In this method, a penalty parameter is used as a regularization parameter, which represents the bias added to the regression coefficient in the equation [44]. The linear regression model that was used in the L1 regularization method is called the least absolute shrinkage and selection operator (LASSO), while the model that used L2 is called a ridge operator [45].…”
Section: Selection Of Groundwater Conditioning Factorsmentioning
confidence: 99%
“…Advances in machine learning (ML) techniques have been mostly utilized in hydrology (Lange and Sippel 2020) and climate research (Huntingford et al 2019) for the prediction and forecasting of environmental variables (Li et al 2011), as well as the optimization of model parameters. Over the last few years, ML approaches have become more common in soil hydrology research to estimate model-derived RZSM using ANNs or satellite-derived SSM using SVMs (Yu et al 2012;Adab et al 2020;Carranza et al 2021). Yu et al (2012) used SVMs and the ensemble particle filter (EnPF) to develop a multi-layer soil moisture prediction model for the Meilin watershed in China, which showed that SVMs are statistically significant and resilient for soil moisture prediction in both the surface and root zone layers.…”
Section: Introductionmentioning
confidence: 99%